2000
DOI: 10.1524/ract.2000.88.9-11.583
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Co(II) and Ni(II)-humate stability constants at high ionic strength NaCl solutions

Abstract: Cobalt / Nickel / Humic substances / Acid dissociation constants / High ionic strengthSummary. Complexation of Ni(II) and Co(II) by unfractionated humic acid (HA) was measured in 0.3 to 5.0 m NaCl solutions at pH 6 and 20 • C, using a solvent extraction technique. The dissociation constants and capacities of the humic acid were investigated in 0.1 to 5.0 m NaCl solutions at 25 • C using potentiometric titration methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…1 presents the curves (α HA vs. pcH) obtained from the titrations of the HA at 0.10 and 3.0 m NaCl. The values of pK a1 and pK a2 of this humic acid were measured previously in this laboratory at I = 0.10, 0.30, 1.0, 3.0 and 5.0 m [17] and values obtained in this work at 0.30 and 5.0 m NaCl were in good agreement. No significant variation occurs in these constants between 0.10 and 5.0 m so the values in Table 2 for the range of ionic strengths were used to obtain the β 1 values.…”
Section: Resultssupporting
confidence: 87%
“…1 presents the curves (α HA vs. pcH) obtained from the titrations of the HA at 0.10 and 3.0 m NaCl. The values of pK a1 and pK a2 of this humic acid were measured previously in this laboratory at I = 0.10, 0.30, 1.0, 3.0 and 5.0 m [17] and values obtained in this work at 0.30 and 5.0 m NaCl were in good agreement. No significant variation occurs in these constants between 0.10 and 5.0 m so the values in Table 2 for the range of ionic strengths were used to obtain the β 1 values.…”
Section: Resultssupporting
confidence: 87%
“…However, different binding behaviors are observed for I > 1 m. Specifically, UO 2 2+ -and Pu 4+ -HA complexation constants increase with increasing ionic strength (Labonne- Wall et al, 1999;Szabò et al, 2010), whereas Co 2+ -HA complexation does not vary substantially, and Ni 2+ -HA complexation slightly decreases (Kurk and Choppin, 2000) with increasing ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, pH measurement is non-trivial in saline solutions. More specifically, "constant pH values" can refer to constant proton activity (pH =log ; Szabò et al, 2010), proton molality (pH m = -log ; Czerwinski et al, 1996;Labonne-Wall et al, 1999;Wall et al, 2002), or constant experimental values, as read on the pHmeter (pH exp ; Kurk and Choppin, 2000; where the pH exp -pH m relationship is provided). Deviation between pH, pH m and pH exp as affected by I may also hamper comparison between different datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of most of these substances possesses functional groups, such as carboxylic, phenolic, hydroxyl, carbonyl, amine, amide, and aliphatic moieties, among others. Because of their polyfunctionality, HAs are considered one of the most powerful chelating agents among existing natural organic substances; they are capable of complexing heavy metals,11, 12 inorganic anions and halides,13, 14 organic acids,15 aromatic compounds,16, 17 pesticides, and herbicides 18, 19. Previous studies have demonstrated the importance of HA interaction with a variety of contaminants; they form complexes of different solubility and chemical and biochemical stability.…”
Section: Introductionmentioning
confidence: 99%